Achieving Thickness‐Insensitive Morphology of the Photoactive Layer for Printable Organic Photovoltaic Cells via Side Chain Engineering in Nonfullerene Acceptors. Issue 14 (21st February 2019) - Lee, Seongyu; Park, Kwang Hun; Lee, Jong‐Hoon; Back, Hyungcheol; Sung, Min Jae; Lee, Jinho; Kim, Jehan; Kim, Heejoo; Kim, Yun‐Hi; Kwon, Soon‐Ki; Lee, Kwanghee
Abstract: Although high power conversion efficiency of over 14% has been achieved using nonfullerene acceptors (NFAs) in organic photovoltaics (OPVs), securing their insensitive device performance to the thickness of the photoactive layer remains an indispensable requirement for their successful commercialization via printing technologies. In this study, by synthesizing a new series of ITIC‐based NFAs having alkyl or alkoxy groups, it is found that the bulk heterojunction morphology dependence on the thickness of the photoactive layer becomes more severe as the difference in the surface energy of the donor and acceptor increases. It is believed that this observation is the origin that yields the device performance dependence on the thickness of the photoactive layer. Through sensitive control of the surface energy of these ITIC‐based NFAs, it is demonstrated that thickness‐insensitive OPVs can be achieved even using a doctor blade technique under air without using any additives. It is believed that present approach provides an important insight into the design of photoactive materials and morphology control for the printable OPVs using NFAs. Abstract : The difference in the surface energy of the donor and acceptor is the origin to determine the sensitivity of bulk heterojunction morphology to the thickness of a photoactive layer . By delicately controlling the surface energy of nonfullerene acceptors via side chain engineering, thickness‐insensitive organic photovoltaics are demonstrated using a doctor blade technique under air without using any additives.